2011
DOI: 10.1088/2041-8205/731/1/l2
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Maxi J1659-152 as a Black Hole Candidate

Abstract: We report on the analysis of all 65 pointed Rossi X-ray Timing Explorer observations of the recently discovered soft X-ray transient MAXI J1659-152 (initially referred to as GRB 100925A). The source was studied in terms of its evolution through the hardness-intensity diagram (HID) as well as its X-ray variability properties. MAXI J1659-152 traced out an anti-clockwise loop in the HID, which is commonly seen in transient low-mass X-ray binaries. The variability properties of the source, in particular the detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
71
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 24 publications
16
71
1
Order By: Relevance
“…A preliminary account of the results can be found in Kuulkers et al (2010bKuulkers et al ( ,d, 2012a and Belloni et al (2010). The MAXI, RXTE and Swift data have already been (partly) described elsewhere, however, the focus was more on the combined spectral and timing behaviour of MAXI J1659−152 (Kalamkar et al 2011;Kennea et al 2011;Muñoz-Darias et al 2011b;Shaposhnikov et al 2012;Yamaoka et al 2012). We find that MAXI J1659−152 is indeed viewed at a high inclination.…”
Section: Introductionsupporting
confidence: 63%
“…A preliminary account of the results can be found in Kuulkers et al (2010bKuulkers et al ( ,d, 2012a and Belloni et al (2010). The MAXI, RXTE and Swift data have already been (partly) described elsewhere, however, the focus was more on the combined spectral and timing behaviour of MAXI J1659−152 (Kalamkar et al 2011;Kennea et al 2011;Muñoz-Darias et al 2011b;Shaposhnikov et al 2012;Yamaoka et al 2012). We find that MAXI J1659−152 is indeed viewed at a high inclination.…”
Section: Introductionsupporting
confidence: 63%
“…It decays in both energy bands as the source evolves toward the SIMS. The two excursions to the SIMS reported by RXTE were accompanied by a drop in the integrated rms in the xte band (see Figure 1 in Kalamkar et al 2011). The first excursion on MJD 55481.7 was not covered by Swift, but after the second transition at MJD 55484.7, the integrated rms was 10.0% ± 2.5% in the hard band (7.1% ± 2.7% in the xte band).…”
Section: Light Curve and Variability Evolutionmentioning
confidence: 88%
“…The peak intensity was observed on MJD 55476.7. Transitions to the SIMS (where a type-B QPO is detected) were observed twice with RXTE (Kalamkar et al 2011); the first excursion to the SIMS on MJD 55481.7 was not observed by Swift, the second transition on MJD 55484.7 was covered by XRT observations but these ended before the transition back to the HIMS on MJD 55501. Kalamkar et al (2011) reported that the source did not make a transition to the HSS (state where spectrum has thermal disk contribution above 75% and the variability is weak; Remillard & McClintock 2006) before returning to the hard state while Muñoz-Darias et al (2011) report the transition of the source to the HSS (softest spectrum dominated by thermal disk component and with weak variability; Belloni 2010).…”
Section: Light Curve and Variability Evolutionmentioning
confidence: 99%
See 2 more Smart Citations